Effect of Workload, Compensation, and Motivation on Employee Performance at Madani Medan General Hospital - Khairunnisa, Zhafira Amriyatti; Bahri, Syaiful; Effendy, Sjahril (Budapest International Research and Critics University, 2021)
This study aims to examine and analyze the effect of workload, compensation and motivation on employee performance at Madani Medan General Hospital. The approach in this assessment is to use a deskriptif and associative approach. In this study, the population was employees at Madani Medan General Hospital, totaling 60 medical personnel, because the number of population used as a sample amounted to 60 medical personnel. The analysis of this research is multiple linear regression. The results showed that workload has a significant effect on employee performance. Compensation has a significant effect on employee performance. Motivation has a significant effect on employee performance. Simultaneously workload, compensation, and motivation have a significant effect on employee performance.